2022
DOI: 10.1101/2022.05.25.493413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

De novo lipogenesis fuels adipocyte autophagosome membrane dynamics

Abstract: SummaryAutophagy is a homeostatic degradative process for cell components that enables stress resilience and can determine cellular fate and function. However, lipid sources for the rapid membrane expansions of autophagosomes, the workhorses of autophagy, are poorly understood. Here, we identify de novo lipogenesis (DNL) as a critical source of fatty acids (FA) to fuel autophagosome dynamics in adipocytes. Adipocyte fatty acid synthase (Fasn) deficiency markedly impairs autophagy, evident by autophagosome accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 55 publications
(87 reference statements)
1
9
0
Order By: Relevance
“…The yeast Acyl-CoA synthetase, Fatty acid activation protein 1 (Faa1), channels fatty acids into de novo phospholipid synthesis and promotes assembly of newly synthesized phospholipids into autophagic membranes 45 . Another paper reported that FASN colocalizes with nascent autophagosomes 17 . A deficiency of FASN in adipocytes, both in vitro and in vivo, markedly impairs autophagy, causing substantial accumulation of autophagosomes 17 .…”
Section: Critical Roles Of Lipogenesis For Autophagymentioning
confidence: 99%
See 2 more Smart Citations
“…The yeast Acyl-CoA synthetase, Fatty acid activation protein 1 (Faa1), channels fatty acids into de novo phospholipid synthesis and promotes assembly of newly synthesized phospholipids into autophagic membranes 45 . Another paper reported that FASN colocalizes with nascent autophagosomes 17 . A deficiency of FASN in adipocytes, both in vitro and in vivo, markedly impairs autophagy, causing substantial accumulation of autophagosomes 17 .…”
Section: Critical Roles Of Lipogenesis For Autophagymentioning
confidence: 99%
“…Another paper reported that FASN colocalizes with nascent autophagosomes 17 . A deficiency of FASN in adipocytes, both in vitro and in vivo, markedly impairs autophagy, causing substantial accumulation of autophagosomes 17 .…”
Section: Critical Roles Of Lipogenesis For Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…It is a complicated metabolic process that is impacted by a number of variables, including nutrition, hormones and genetics. The hormone insulin, which is secreted in reaction to elevated blood glucose levels, plays a major role in controlling lipogenesis (Ladeira et al., 2016b; Rowland et al., 2023; Saponaro et al., 2015). De novo lipogenesis, a process that insulin accelerates, is a process that enhances the conversion of glucose into fatty acids in adipose tissue.…”
Section: Transcription Factors In Adipogenesis and Lipogenesismentioning
confidence: 99%
“…De novo lipogenesis, a process that insulin accelerates, is a process that enhances the conversion of glucose into fatty acids in adipose tissue. After that, the fatty acids are converted into triglycerides and kept in adipose tissue (Rowland et al., 2023; Yue et al., 2018). For fat deposition and metabolism in beef cattle, the interaction between adipogenesis and lipogenesis is essential.…”
Section: Transcription Factors In Adipogenesis and Lipogenesismentioning
confidence: 99%